PERAN ORANG TUA DALAM PENDIDIKAN KARAKTER PESERTA DIDIK SEKOLAH DASAR - Sitti Widatul Hasanah; Eka Fitri Nindiatus Sholehah; Riska Ahwa Anggraeni; Desi Ummi Rusdiana (Pendidikan Fisika FKIP UNEJ, 2022)
This study focuses on the role of parents in improving the character education of elementary school students. Where parents play an important role in shaping the character of students at elementary school age. The purpose of this study is to educate parents and the general public to pay more attention to children at elementary school age. Like building good communication with children. This research method uses a discussion method in the form of a descriptive analytical method and a library research approach, by examining books, magazines, and other reading sources. The results of the study indicate that a very strategic role in optimizing character education for elementary school students is the role of parents. The effectiveness of the role of parents is very influential on the character of students. In this way, the family environment can become an important pattern in civilizing the nation's character, especially students who are at the elementary school level. An example of the role of parents that can be applied to elementary school students and starting from the simplest, namely, by instilling habits (habituations) about what is good and what is wrong and being able to feel well (moral feeling).